Formation and Development of Self-Organizing Intelligent Technologies of Inductive Modeling - Stepashko, V.S. (Кибернетика и вычислительная техника, 2018)
The purpose of this paper is analysing the background of the GMDH invention by Ivakhnenko and the evolution of model self-organization ideas, methods and tools during the halfcentury historical period of successful development of the inductive modeling methodology.